(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Endometriosis is frequently associated with gastrointestinal symptoms, inaddition to dysmenorrhoea, dyspareunia and infertility. Gastrointestinal tract is not alwaysinvolved when gastrointestinal symptoms are present. Method: A cross sectional study was conducted in the department of Obstetrics &Gynaecology of Bangladesh Sheikh Mujib Medical University (BSMMU) on 55 infertile womenwith surgical diagnosis of endometriosis with the objective to determine the frequency ofgastrointestinal symptoms in our population of women with endometriosis and to find outwhether they were relevant to severity of endometriosis. Results: There was a high prevalence (37.5%) of gastrointestinal symptoms in women withendometriosis. Bloating was the most frequent gastrointestinal symptom. Among the womenwith severe stage IV endometriosis, 57.6% had gastrointestinal symptoms. Conclusion: A gynecologist must consider the gastrointestinal symptoms while dealing withthe women with endometriosis. Further evaluation of gastrointestinal tract involvement isnecessary for counseling and comprehensive management of the women with endometriosis. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 140-142